Nano enzyme, preparation method and application thereof, and glucose concentration detection method
Ru/Co-N,Zn-CNCs nanomaterials combined with glucose oxidase were prepared by calcining and reducing methods, and a cascade reaction colorimetric sensor was constructed, which solved the problem of low nanoenzyme activity, achieved high sensitivity glucose detection, and simplified The operation process and reduce costs are suitable for the determination of blood sugar concentration in human serum.
Patent Information
- Application Number
- CN202411287287.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-14
AI Technical Summary
The existing glucose detection technology has shortcomings in terms of operational convenience, cost control and detection speed. The activity of nanoenzymes also limits its wide application, especially the enzyme-like activity of metal-supported nitrogen-doped carbon materials is relatively low, and the catalytic efficiency is Not ideal.
Ru/Co-N,Zn-CNCs nanomaterials were prepared by calcining and reducing methods, and combined with glucose oxidase to construct a cascade reaction colorimetric sensor, which generated synergistic effects through doping of Ru metals, improved catalytic activity, and achieved the Ultrasensitive colorimetric detection of glucose.
It realizes sensitive detection of glucose in the range of 10-2000μM, with the detection limit as low as 0.61μM, showing excellent stability and linear response characteristics, simplifying the operation process, saving time and energy, and is suitable for the determination of blood sugar concentration in human serum.
Smart Images

Figure CN119307462A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of glucose concentration detection, and in particular to a nanozyme and a preparation method and application thereof, and a glucose concentration detection method. Background Art
[0002] Glucose is an important substance for maintaining life activities and is widely present in nature. It plays a vital role in organisms, providing energy for cell metabolism and biosynthesis. However, when the level of glucose in the body is abnormal, it may lead to a series of serious health problems, including high blood pressure, diabetes, cardiovascular disease and cancer.
[0003] At present, the technologies for detecting glucose mainly include high performance liquid chromatography, electrochemical sensors, gas chromatography and fluorescence spectroscopy. Although these methods have excellent performance in detection accuracy, they are insufficient in terms of operational convenience, cost control and detection speed, which limits their application in rapid detection. In contrast, the colorimetric detection technology based on nanozymes has gradually become a powerful tool for rapid detection of glucose due to its simplicity, speed and high cost-effectiveness. However, the activity of nanozymes often limits the widespread application of this technology, which is a technical bottleneck that needs to be overcome urgently.
[0004] In recent years, metal-organic framework (MOF) nanomaterials have become ideal candidates for the preparation of high-performance nanozymes due to their unique high specific surface area, high porosity and structural adjustability. In particular, imidazolide zeolite metal-organic framework (ZIF) has attracted widespread attention due to its simple synthesis, high nitrogen content and good stability. By using MOF as a template, researchers have successfully prepared metal-loaded nitrogen-doped carbon materials, which can not only improve the electron transfer efficiency and conductivity of metals, but also prevent metal aggregation and reduce the loss of active sites. Among them, cobalt-nitrogen and zinc-doped carbon nanocube composites (Co-N, Zn-CNCs) synthesized using ZIF-67 as a template have been successfully developed. However, the enzyme-like activity of this material is still low and the catalytic efficiency is not ideal. Therefore, it is necessary to explore new improvement methods to improve the activity of nanozymes and thus enhance their catalytic effect in glucose detection. Summary of the invention
[0005] The purpose of the present invention is to solve the problem of low catalytic efficiency of nanozymes in the background technology, and to propose a nanozyme and its preparation method and application, and a method for detecting glucose concentration.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a nanozyme, comprising the following steps:
[0008] Dissolving Co salt, Zn salt, 2-methylimidazole and hexadecyltrimethylammonium bromide in water, reacting, and separating to obtain a precipitate;
[0009] calcining the precipitate under an inert atmosphere to obtain a calcined product;
[0010] The calcined product and Ru salt are added to ethylene glycol, heated for reaction, and separated to obtain nanomaterials;
[0011] The nanomaterial and glucose oxidase are dissolved in water, stirred, and separated to obtain the nanozyme.
[0012] Preferably, the Co salt comprises Co(NO 3 ) 2 、Co(CH 3 COO 2 、CoSO 4 、CoCl 2 At least one of;
[0013] And / or, the Zn salt comprises Zn(NO 3 ) 2 、ZnSO 4 、ZnCl 2 At least one of;
[0014] And / or, the Ru salt comprises RuCl 3 ,Ru(NO)(NO 3 ) 3 NH 4 ) 2 RuCl 6 、[Ru(NH 3 ) 6 ]Cl 3 At least one of .
[0015] Preferably, Co salt, Zn salt, 2-methylimidazole and hexadecyltrimethylammonium bromide are dissolved in water, reacted for 10 to 15 hours, and filtered to obtain a precipitate; the precipitate is washed, dried, and then calcined under an inert atmosphere to obtain a calcined product;
[0016] Wherein, the molar ratio of Co salt, Zn salt, 2-methylimidazole and hexadecyltrimethylammonium bromide is (45-55):(140-160):(5-7):(1000-1100);
[0017] The molar volume ratio of Co salt and water is (9×10 -6 ~1.1×10 -5 )mol:(160~170)mL.
[0018] Preferably, the precipitate is calcined under an inert atmosphere to obtain a calcined product, specifically comprising: heating the precipitate from room temperature to 700-800° C. at a rate of 5-7° C. / min under an inert atmosphere, calcining for 2-3 hours, and then cooling to room temperature to obtain a calcined product;
[0019] The inert atmosphere includes at least one of nitrogen, helium, neon and argon.
[0020] Preferably, the calcined product and Ru salt are added to ethylene glycol, heated at 170-180° C. for 3-5 hours, and filtered to obtain the nanomaterial;
[0021] Dissolve the nanomaterial and glucose oxidase in water, stir for 2 to 3 hours, and filter to obtain the nanozyme;
[0022] The mass ratio of the calcined product to the Ru salt is (8-10):(5-6), and the mass volume ratio of the Ru salt to the ethylene glycol is (25-30) mg:(50-55) mL;
[0023] The mass ratio of the nano material to the glucose oxidase is (2-3):(1-2), and the mass volume ratio of the glucose oxidase to water is (10-20) mg:(60-65) mL.
[0024] In a second aspect, the present invention also provides a nanozyme prepared by the preparation method.
[0025] In a third aspect, the present invention also provides an application of the nanozyme in detecting glucose concentration.
[0026] In a fourth aspect, the present invention further provides a method for detecting glucose concentration, comprising the following steps:
[0027] Adding the nanozyme and TMB to the test solution to obtain a mixed solution;
[0028] Add acetic acid-sodium acetate buffer to the mixed solution, incubate, and measure the absorbance at 652 nm;
[0029] The glucose concentration was detected by absorbance.
[0030] Preferably, the volume ratio of the mixed solution to the acetic acid-sodium acetate buffer is (3-5):(17-20);
[0031] The pH value of the acetic acid-sodium acetate buffer is 4.0 to 6.0;
[0032] The incubation temperature is 20-40° C. and the incubation time is 20-25 min.
[0033] Preferably, the concentration of nanozyme in the mixed solution is 0.02-0.1 mg / mL;
[0034] The concentration of TMB in the mixed solution is 2-10 mM.
[0035] The nanozyme, preparation method and application thereof, and glucose concentration detection method of the present invention have the following beneficial effects compared with the prior art:
[0036] The present invention adopts calcination and reduction methods to prepare Ru / Co-N, Zn-CNCs nanomaterials, which can quickly catalyze the oxidation reaction of TMB in the presence of hydrogen peroxide, and by combining with glucose oxidase, a cascade reaction colorimetric sensor for glucose detection is successfully constructed. This preparation method is not only simple to operate, but also economical and efficient; due to the synergistic effect generated by the doping of Ru metal, the nanoenzyme has better catalytic activity, and by combining with glucose oxidase, the system can achieve ultra-sensitive colorimetric detection of glucose, showing excellent stability and linear response characteristics, and further improving the accuracy of detection. The one-step detection method is used in the present invention, which simplifies the operation process and saves time and energy. Through colorimetric detection, the method can sensitively detect glucose in the range of 10-2000 μM, and the detection limit is as low as 0.61 μM. At the same time, the sensor shows good selectivity for glucose. When further applied to the determination of blood glucose concentration in human serum, the method obtains satisfactory results, demonstrating its wide potential in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 The schematic diagram of the Ru / Co-N,Zn-CNCs-GOx nanoenzyme prepared by the present invention for detecting glucose;
[0039] Figure 2 The performance and structure characterization of the Ru / Co-N, Zn-CNCs nanomaterials prepared in step S3 of Example 1;
[0040] Figure 3 The XRD spectrum of the Ru / Co-N, Zn-CNCs nanomaterial prepared in step S3 of Example 1;
[0041] Figure 4 The XPS spectrum of the Ru / Co-N, Zn-CNCs nanomaterial prepared in step S3 of Example 1;
[0042] Figure 5 Schematic diagram of the catalytic mechanism analysis of the Ru / Co-N, Zn-CNCs nanomaterials prepared in step S3 of Example 1;
[0043] Figure 6 Optimization diagram of glucose concentration detection conditions according to the method in Example 2;
[0044] Figure 7 The Ru / Co-N, Zn-CNCs nanomaterials prepared in step S3 of Example 1 react with TMB and H 2 O 2 Schematic diagram of the kinetic test;
[0045] Figure 8 Schematic diagram of UV-visible colorimetric sensing analysis of glucose;
[0046] Fig. 9 This is a comparison chart of the selectivity for detecting glucose. DETAILED DESCRIPTION
[0047] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.
[0048] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any quoted numbers (fractions or integers) within the indicated range.
[0050] The present invention provides a method for preparing a nanozyme, comprising the following steps:
[0051] S1, dissolving Co salt, Zn salt, 2-methylimidazole and hexadecyltrimethylammonium bromide in water, reacting, and separating to obtain a precipitate;
[0052] S2, calcining the precipitate under an inert atmosphere to obtain a calcined product;
[0053] S3, adding the calcined product and Ru salt into ethylene glycol, heating for reaction, and separating to obtain nanomaterials;
[0054] S4. Dissolve the nanomaterials and glucose oxidase in water, stir, and separate to obtain nanozymes.
[0055] The present invention prepares Ru / Co-N, Zn-CNCs nanomaterials by calcination and reduction methods, and then loads glucose oxidase (GOx) onto the Ru / Co-N, Zn-CNCs nanomaterials to obtain cascade nanozyme Ru / Co-N, Zn-CNCs-GOx.
[0056] In some embodiments, the Co salt includes Co(NO 3 ) 2 、Co(CH 3 COO 2 、CoSO 4 、CoCl 2 At least one of .
[0057] In some embodiments, the Zn salt includes Zn(NO 3 ) 2 、ZnSO 4 、ZnCl 2 At least one of;
[0058] In some embodiments, the Ru salt includes RuCl 3 ,Ru(NO)(NO 3 ) 3 NH 4 ) 2 RuCl 6 、[Ru(NH 3 ) 6 ]Cl 3 At least one of .
[0059] In some embodiments, Co salt, Zn salt, 2-methylimidazole and hexadecyltrimethylammonium bromide are dissolved in water in a molar ratio of (45-55):(140-160):(5-7):(1000-1100), and the mixture is allowed to react at room temperature (25°C) for 10-15 hours, and a precipitate is obtained by filtration; the precipitate is washed and dried, and then calcined under an inert atmosphere to obtain a calcined product; the molar volume ratio of Co salt to water is (9×10 -6 ~1.1×10 -5 )mol:(160~170)mL.
[0060] In some embodiments, the precipitate is calcined under an inert atmosphere to obtain a calcined product, specifically comprising: heating the precipitate from room temperature (25°C) to 700-800°C at a rate of 5-7°C / min under an inert atmosphere, calcining for 2-3h, and then cooling to room temperature to obtain a calcined product.
[0061] In some embodiments, the inert atmosphere includes at least one of nitrogen, helium, neon, and argon.
[0062] In some embodiments, the calcined product and Ru salt are added to ethylene glycol in a mass ratio of (8-10):(5-6), heated at 170-180°C for 3-5 hours, and filtered to obtain the nanomaterial; the mass volume ratio of Ru salt to ethylene glycol is (25-30) mg:(50-55) mL.
[0063] In some embodiments, nanomaterials and glucose oxidase are dissolved in water in a mass ratio of (2-3):(1-2), stirred at room temperature (25°C) for 2-3 hours, and filtered to obtain nanozyme. The mass volume ratio of glucose oxidase to water is (10-20) mg:(60-65) mL.
[0064] Based on the same inventive concept, the present invention also provides a nanozyme prepared by the above-mentioned preparation method.
[0065] Based on the same inventive concept, the present invention also provides an application of the above-mentioned nanozyme in detecting glucose concentration.
[0066] Based on the same inventive concept, the present invention also provides a method for detecting glucose concentration, comprising the following steps:
[0067] S1. Add the above-mentioned nanozyme and TMB (3,3',5,5'-tetramethylbenzidine) to the test solution to obtain a mixed solution;
[0068] S2, adding acetic acid-sodium acetate buffer to the mixed solution, incubating, and measuring the absorbance at 652 nm;
[0069] S3. Detect the glucose concentration based on the absorbance.
[0070] The principle of the glucose concentration detection method of the present invention is as follows: Figure 1 As shown in Figure 2, under the action of Ru / Co-N,Zn-CNCs-GOx nanozymes, glucose is oxidized into gluconic acid and H 2 O 2 Then, under the action of nanozymes, H 2 O 2 It continues to decompose into ROS (reactive oxygen species), which can cause the substrate TMB to change color and have absorbance at 652nm. The cascade catalytic reaction of Ru / Co-N, Zn-CNCs-GOx nanozymes is used to achieve high-sensitivity and high-selectivity detection of glucose.
[0071] In some embodiments, the volume ratio of the mixed solution to the acetic acid-sodium acetate buffer is (3-5):(17-20).
[0072] In some embodiments, the pH value of the acetic acid-sodium acetate buffer is 4.0-6.0.
[0073] In some embodiments, the incubation temperature is 20-40° C. and the incubation time is 20-25 min.
[0074] In some embodiments, the concentration of nanozyme in the mixed solution is 0.02-0.1 mg / mL.
[0075] In some embodiments, the concentration of TMB in the mixed solution is 2-10 mM.
[0076] In some embodiments, the method for detecting glucose concentration comprises the following steps:
[0077] S1. The Ru / Co-N, Zn-CNCs-GOx nanozyme is added to water to obtain a nanozyme solution with a concentration of 0.1 mg / mL; TMB is added to water to obtain a TMB solution with a concentration of 10 mM;
[0078] Mixing equal volumes of the nanozyme solution, the TMB solution, and the test solution containing 10-2000 μM glucose to obtain a mixed solution;
[0079] S2, adding acetic acid-sodium acetate buffer to the mixed solution, incubating, and testing the UV-Vis (ultraviolet-visible absorption spectrum) absorbance at 652 nm;
[0080] S3. Detect the glucose concentration based on the absorbance.
[0081] The present invention adopts calcination and reduction methods to prepare Ru / Co-N, Zn-CNCs nanomaterials, which can quickly catalyze the oxidation reaction of TMB in the presence of hydrogen peroxide, and by combining with glucose oxidase, a cascade reaction colorimetric sensor for glucose detection is successfully constructed. This preparation method is not only simple to operate, but also economical and efficient; due to the synergistic effect generated by the doping of Ru metal, the nanoenzyme has better catalytic activity, and by combining with glucose oxidase, the system can achieve ultra-sensitive colorimetric detection of glucose, showing excellent stability and linear response characteristics, and further improving the accuracy of detection. The one-step detection method is used in the present invention, which simplifies the operation process and saves time and energy. Through colorimetric detection, the method can sensitively detect glucose in the range of 10-2000 μM, and the detection limit is as low as 0.61 μM. At the same time, the sensor shows good selectivity for glucose. When further applied to the determination of blood glucose concentration in human serum, the method obtains satisfactory results, demonstrating its wide potential in practical applications.
[0082] The following further illustrates the nanozyme of the present application and its preparation method and application, and the glucose concentration detection method with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0083] Example 1
[0084] The present invention provides a method for preparing a nanozyme, comprising the following steps:
[0085] S1, Co(NO 3 ) 2 6H 2 O、Zn(NO 3 ) 2 6H 2 O, 2-methylimidazole and hexadecyltrimethylammonium bromide were dissolved in water at a molar ratio of 50:150:5:1100, and the mixture was allowed to react at room temperature (25°C) for 12 hours, and the precipitate was filtered to obtain the product; among them, Co(NO 3 ) 2 6H 2 The molar volume ratio of O to water is 1×10 -5 mol:160mL;
[0086] S2, washing and drying the precipitate, then heating from room temperature to 700°C at a rate of 5°C / min under a nitrogen atmosphere, calcining for 2h, and then cooling to room temperature to obtain a calcined product;
[0087] S3, calcined product and RuCl 3 The mixture was mixed in a mass ratio of 8:5, added to ethylene glycol, and refluxed for 3 h in an oil bath at 170 °C. The Ru / Co-N, Zn-CNCs nanomaterials were separated by filtration. RuCl 3 The mass volume ratio with ethylene glycol is 25mg:50mL;
[0088] S4, Ru / Co-N, Zn-CNCs nanomaterials and glucose oxidase were dissolved in H 2 O and stirred for 2 hours, and filtered to separate the Ru / Co-N,Zn-CNCs-GOx cascade nanozyme; the mass volume ratio of glucose oxidase to water was 10 mg:60 mL.
[0089] Example 2
[0090] The present application embodiment provides a method for detecting glucose concentration, comprising the following steps:
[0091] S1. Add the Ru / Co-N,Zn-CNCs-GOx nanozyme prepared in Example 1 into water to obtain a nanozyme solution with a concentration of 0.1 mg / mL; add TMB into water to obtain a TMB solution with a concentration of 10 mM;
[0092] Mixing equal volumes of the nanozyme solution, the TMB solution, and the test solution containing 10-2000 μM glucose to obtain a mixed solution;
[0093] S2. Add acetic acid-sodium acetate buffer to the mixed solution, incubate for 20 min, and measure the UV-Vis (ultraviolet-visible absorption spectrum) absorbance at 652 nm; the volume ratio of the mixed solution to the acetic acid-sodium acetate buffer is 3:17;
[0094] S3. Detect the glucose concentration based on the absorbance.
[0095] Performance Characterization
[0096] Figure 2 The performance and structure characterization of the Ru / Co-N, Zn-CNCs nanomaterials prepared in step S3 of Example 1;
[0097] Figure 2 A is: Ru / Co-N, Zn-CNCs nanomaterials in acetic acid-sodium acetate buffer solution with pH = 5.0 and TMB+H 2 O 2 The UV spectrum measured by the reaction; Specifically, a in A is the Ru / Co-N, Zn-CNCs nanomaterial solution (concentration 0.1 mg / mL, the solvent used is water), H 2 O2 a) solution (concentration 50 mM, the solvent used is water), TMB solution (concentration 10 mM, the solvent used is water), and pH = 5.0 acetic acid-sodium acetate buffer solution were mixed at room temperature in a volume ratio of 1:1:1:17, incubated for 20 min, and the absorbance at 652 nm was tested; b) Ru / Co-N, Zn-CNCs nanomaterial solution (concentration 0.1 mg / mL, the solvent used is water), TMB solution (concentration 10 mM, the solvent used is water), and pH = 5.0 acetic acid-sodium acetate buffer solution were mixed at room temperature in a volume ratio of 1:1:18, incubated for 20 min, and the absorbance at 652 nm was tested; c) H 2 O 2 Solution (concentration 50 mM, the solvent used is water), TMB solution (concentration 10 mM, the solvent used is water), and acetic acid-sodium acetate buffer solution of pH = 5.0 were mixed at room temperature in a volume ratio of 1:1:18, incubated for 20 minutes, and the absorbance at 652 nm was measured;
[0098] Figure 2 B is the SEM image of the Ru / Co-N, Zn-CNCs nanomaterial prepared in step S3 of Example 1.
[0099] Figure 2 C is the TEM image of the Ru / Co-N, Zn-CNCs nanomaterial prepared in step S3 of Example 1.
[0100] Figure 2 D in the figure is the STEM image of the Ru / Co-N, Zn-CNCs nanomaterial prepared in step S3 of Example 1.
[0101] Figure 2 E in FIG. 1 is the HAADF-STEM-EDS elemental mapping diagram of the Ru / Co-N, Zn-CNCs nanomaterials prepared in step S3 in Example 1.
[0102] from Figure 2 As can be seen in A, Ru / Co-N, Zn-CNCs nanomaterials, acetic acid-sodium acetate buffer solution with pH = 5.0, H 2 O 2 After being mixed with TMB, it has an extremely high absorbance at 652 nm. Therefore, the Ru / Co-N,Zn-CNCs nanomaterial of the present invention can be used to detect glucose concentration.
[0103] from Figure 2 The transmission electron microscope image shows that the Ru / Co-N, Zn-doped carbon nanocube nanozyme catalytic material was successfully prepared.
[0104] Figure 3This is the XRD spectrum of the Ru / Co-N, Zn-CNCs nanomaterial prepared in step S3 of Example 1.
[0105] from Figure 3 It can be seen that the diffraction peak at 44.21° corresponds to the (111) plane of the metal Co phase (JCPDS No. 15-0806). The peaks at 42.15° and 44.01° correspond to the (002) and (101) planes of the metal Ru phase, respectively (JCPDS No. 06-0663), which confirms the successful synthesis of metal Ru and Co in the material.
[0106] Figure 4 It is the XPS spectrum of the Ru / Co-N, Zn-CNCs nanomaterial prepared in step S3 in Example 1, wherein A is: the full XPS spectrum of the Ru / Co-N, Zn-CNCs nanomaterial, B is: the XPS spectrum at C 1s and Ru 3d, C is: the XPS spectrum at Zn 2p; D is: the XPS spectrum at Co 2p; E is: the XPS spectrum at N 1s; F is: the XPS spectrum at O 1s.
[0107] XPS analysis revealed the chemical state of each element in the material and its binding energy, and further confirmed its surface chemical state.
[0108] Figure 5 Schematic diagram of the catalytic mechanism analysis of Ru / Co-N, Zn-CNCs nanomaterials prepared in step S3 of Example 1.
[0109] Specifically, different concentrations of isopropanol, tryptophan or 1,4-benzoquinone were added to a mixture of TMB, H 2 O 2 , Ru / Co-N, Zn-CNCs nanomaterial suspension and acetic acid-sodium acetate buffer, incubated at room temperature for 3 minutes, and recorded the absorbance at different wavelengths; 2 O 2 The preparation method of the Ru / Co-N, Zn-CNCs nanomaterial suspension and acetic acid-sodium acetate buffer is as follows: Ru / Co-N, Zn-CNCs nanomaterial solution (concentration 0.1 mg / mL, the solvent used is water), H 2 O 2 The solution (concentration 50 mM, the solvent used is water), the TMB solution (concentration 10 mM, the solvent used is water), and the acetic acid-sodium acetate buffer solution with a pH of 5.0 are mixed at a volume ratio of 1:1:1:16 at room temperature.
[0110] Figure 5A is a schematic diagram of the absorbance change after adding different concentrations (the concentrations are 0 mM, 1 mM, 2 mM, 3 mM, and 5 mM) of isopropanol (added in the form of isopropanol aqueous solution);
[0111] Figure 5 B is a schematic diagram of the absorbance change after adding tryptophan (added in the form of tryptophan aqueous solution) at different concentrations (the concentrations are 0 mM, 1 mM, 2 mM, 3 mM, and 5 mM, respectively);
[0112] Figure 5 C is a schematic diagram of the absorbance change after adding different concentrations (the concentrations are 0 mM, 1 mM, 2 mM, 3 mM, and 5 mM) of 1,4-benzoquinone (added in the form of 1,4-benzoquinone aqueous solution);
[0113] Figure 5 D in the middle is the EPR (electron paramagnetic resonance) image;
[0114] Figure 5 The catalytic mechanism of Ru / Co-N,Zn-CNCs nanomaterials was analyzed. In order to explore the catalytic mechanism of its POD-like activity, the catalytic intermediates, including tryptophan, 1,4-benzoquinone and isopropanol, were studied in detail, respectively as singlet oxygen ( 1 O 2 ), superoxide anion (O 2 ·- ) and hydroxyl radical (·OH) scavengers. Isopropanol has little effect on the TMB oxidation reaction catalyzed by Ru / Co-N,Zn-CNCs, indicating that ·OH radicals have almost no involvement in the catalytic process. However, the increase in tryptophan and 1,4-benzoquinone concentrations significantly inhibited the catalytic reaction. The results show that 1 O 2 and O 2 ·- It is the main ROS involved in the catalytic oxidation of TMB. Finally, EPR test was performed to provide more reliable data support.
[0115] Further, according to the method in Example 2, the glucose concentration detection conditions were optimized, and the results were as follows: Figure 6 shown. Figure 6A is the relative activity of Ru / Co-N, Zn-CNCs nanozymes in acetic acid-sodium acetate buffer solutions with different pH values (pH values are 2.0, 3.0, 4.0, 5.0, 6.0, and 7.0, respectively, and the fixed incubation temperature is 30°C); B is the relative activity of Ru / Co-N, Zn-CNCs nanozymes at different incubation temperatures (temperatures are 20°C, 30°C, 40°C, 50°C, and 60°C, respectively, and the fixed pH value of the acetic acid-sodium acetate buffer solution is 5.0). The relative activity is the activity under the relative optimal conditions after normalization based on the absorbance data, for example Figure 6 The relative activity in A was 100% when the pH was 5.0, and it was calculated based on the normalized absorbance data at other pH values.
[0116] from Figure 6 It can be seen that by changing the pH value of the buffer solution, when the pH is 5.0, the catalytic activity of Ru / Co-N, Zn-CNCs nanomaterials reaches the highest, so the optimal pH of the buffer solution is 5.0; by changing the incubation temperature, when the incubation is 30℃, the catalytic activity of Ru / Co-N, Zn-CNCs nanomaterials reaches the highest, so the optimal incubation temperature is 30℃.
[0117] Figure 7 The Ru / Co-N, Zn-CNCs nanomaterials prepared in step S3 of Example 1 react with TMB and H 2 O 2 Schematic diagram of the kinetic test; Specifically, the test method is: Ru / Co-N, Zn-CNCs nanomaterial solution (concentration 0.1 mg / mL, the solvent used is water), H 2 O 2 Solution (concentrations were 1 mM, 2 mM, 5 mM, 8 mM, 10 mM, respectively, and the solvent used was water), TMB solution (concentrations were 0.75 mM, 1.0 mM, 1.5 mM, 2.0 mM, 2.5 mM, respectively, and the solvent used was water), and acetic acid-sodium acetate buffer solution with a pH of 5.0 were mixed at a volume ratio of 1:1:1:17 at room temperature, incubated for 20 min, and tested the absorbance at 652 nm.
[0118] Figure 7 A: Michaelis-Menten fitting diagram of Ru / Co-N, Zn-CNCs nanomaterials to TMB;
[0119] Figure 7 B: Lineweaver-Burk curves of Ru / Co-N, Zn-CNCs nanomaterials to TMB;
[0120] Figure 7C is the Ru / Co-N, Zn-CNCs nanomaterials for H 2 O 2 Michaelis-Menten fitting plot of ;
[0121] Figure 7 D is: Ru / Co-N, Zn-CNCs nanomaterials for H 2 O 2 Lineweaver-Burk curve plot.
[0122] Figure 7 The results of the kinetic tests are shown. In order to verify the affinity of the material to the substrate, UV-visible spectroscopy was used to analyze the affinity of TMB and H 2 O 2 By changing the concentration of TMB or H 2 O 2 The concentration of H 2 O 2 The concentration is 50mM; when changing H 2 O 2 When the concentration of TMB was fixed at 50 mM, the measurement was performed at 652 nm for 180 s. Figure 6 The Michaelis-Menten fitting curve and Lineweaver-Burk curve in the figure can be used to calculate the Ru / Co-N, Zn-CNCs nanozyme's effect on H 2 O 2 The results are shown in Table 1:
[0123] Table 1- Comparison of kinetic parameters of horseradish peroxidase and Ru / Co-N,Zn-CNCs nanozyme catalysts
[0124]
[0125] As shown in Table 1 above, compared with HRP (where the kinetic parameters of HRP are obtained according to existing literature L. Gao, J. Zhuang, L. Nie, J. Zhang, Y. Zhang, N. Gu, T. Wang, J. Feng, D. Yang, S. Perrett, X. Yan, Intrinsic peroxidase-like activity offerromagnetic nanoparticles), Ru / Co-N, Zn-CNCs nanozymes have a stronger activity against H 2 O 2It shows a higher affinity, but the affinity of nanozymes to TMB is lower than that of HRP, which indicates that the catalytic process of Ru / Co-N,Zn-CNCs nanozymes is similar to that of natural enzymes and follows the ping-pong mechanism.
[0126] Figure 8 The UV-visible colorimetric sensor analysis of glucose was carried out. Specifically, the method in Example 2 was used to test the glucose under the optimal conditions: the pH of the acetic acid-sodium acetate buffer was 5.0, and the incubation temperature was 30°C; Figure 8 As shown in the figure, with the increase of glucose concentration, the absorbance of the system at 652nm increased significantly. When the glucose concentration ranged from 10μM to 2000μM, a good linear relationship was obtained. These results show that the colorimetric sensor based on Ru / Co-N,Zn-CNCs is feasible in the determination of glucose.
[0127] Fig. 9 The specificity of Ru / Co-N,Zn-CNCs nanozymes was verified through selectivity testing.
[0128] like Fig. 9 As shown, from left to right are blank, sucrose, D-fructose, uric acid, maltose, lactose, galactose and glucose. In the control group, the concentrations of sucrose, D-fructose, uric acid, maltose, lactose and galactose are 10 times that of glucose, but the absorbance of glucose is still significantly higher than these control groups. This shows that the constructed nanoenzyme detection system has good selectivity for glucose.
[0129] The test method of the blank group is as follows: the Ru / Co-N,Zn-CNCs-GOx nanozyme prepared in Example 1 is added to water to obtain a nanozyme solution with a concentration of 0.1 mg / mL; TMB is added to water to obtain a TMB solution with a concentration of 10 mM; the nanozyme solution, TMB solution and water are mixed in equal volumes to obtain a mixed solution; acetic acid-sodium acetate buffer (pH 5.0) is added to the mixed solution, incubated at 30°C for 20 minutes, and the UV-Vis (ultraviolet-visible absorption spectrum) absorbance at 652 nm is tested; the volume ratio of the mixed solution to the acetic acid-sodium acetate buffer is 3:17;
[0130] The test methods for sucrose, D-fructose, uric acid, maltose, lactose, galactose and glucose are as follows (sucrose is used as an example for explanation, and other substances are tested with reference to sucrose). Taking sucrose as an example, Fig. 9The specific test method is as follows: the Ru / Co-N,Zn-CNCs-GOx nanozyme prepared in Example 1 is added to water to obtain a nanozyme solution with a concentration of 0.1 mg / mL; TMB is added to water to obtain a TMB solution with a concentration of 10 mM; the nanozyme solution, TMB solution and sucrose (10 mM, the solvent used is water) are mixed in equal volumes to obtain a mixed solution; acetic acid-sodium acetate buffer (pH 5.0) is added to the mixed solution, incubated at 30°C for 20 minutes, and the UV-Vis (ultraviolet-visible absorption spectrum) absorbance at 652 nm is tested; the volume ratio of the mixed solution to the acetic acid-sodium acetate buffer is 3:17;
[0131] Example 3
[0132] Detection of Glucose in Serum Samples
[0133] In order to verify the accuracy and practicality of Ru / Co-N,Zn-CNCs-GOx nanozymes in practical applications, human serum samples were tested by standard addition method. The serum pretreatment method is as follows: the serum supernatant is diluted 100 times with PBS buffer solution (0.1M, pH 7.4); then, different concentrations of glucose (100μM, 500μM and 1000μM) are added to the treated serum sample to obtain a test solution containing; the specific test method is as follows:
[0134] The Ru / Co-N,Zn-CNCs-GOx nanozyme prepared in Example 1 was added to water to obtain a nanozyme solution with a concentration of 0.1 mg / mL; TMB was added to water to obtain a TMB solution with a concentration of 10 mM; the nanozyme solution, the TMB solution and the test solution containing glucose were mixed in equal volumes to obtain a mixed solution;
[0135] Acetic acid-sodium acetate buffer (pH 5.0) was added to the mixed solution, incubated at 30°C for 20 minutes, and the UV-Vis (ultraviolet-visible absorption spectrum) absorbance at 652nm was tested; the volume ratio of the mixed solution to acetic acid-sodium acetate buffer was 3:17; and the concentration of glucose in the serum was determined by substituting the absorbance intensity value into the linear relationship formula. The test results are shown in Table 2.
[0136] Table 2 - Detection results of glucose in human serum samples
[0137]
[0138] According to the data in Table 2, the developed glucose sensor performed well in terms of recovery, ranging from 99.39% to 102.79%, while the relative standard deviation was less than 3.48%, which showed that the accuracy and precision of the sensor in glucose analysis were effectively guaranteed.
[0139] According to Examples 1 to 3, the glucose colorimetric analysis method of Ru / Co-N,Zn-CNCs-GOx nanozyme of the present invention is not only applicable to actual sample detection, but also has low detection limit, excellent selectivity and reliability. In addition, the method is easy to operate, saving time and cost.
[0140] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nanozyme, characterized in that: The following steps are involved: Dissolving Co salt, Zn salt, 2-methylimidazole and hexadecyltrimethylammonium bromide in water, reacting, and separating to obtain a precipitate; calcining the precipitate under an inert atmosphere to obtain a calcined product; The calcined product and Ru salt are added to ethylene glycol, heated for reaction, and separated to obtain nanomaterials; The nanomaterial and glucose oxidase are dissolved in water, stirred, and separated to obtain the nanozyme.
2. The method for preparing the nanozyme according to claim 1, characterized in that: The Co salt includes at least one of Co(NO3)2, Co(CH3COO)2, CoSO4, and CoCl2; And / or, the Zn salt includes at least one of Zn(NO3)2, ZnSO4, and ZnCl2; And / or, the Ru salt includes at least one of RuCl3, Ru(NO)(NO3)3, (NH4)2RuCl6, and [Ru(NH3)6]Cl3.
3. The method for preparing the nanozyme according to claim 1, characterized in that: Dissolve Co salt, Zn salt, 2-methylimidazole and hexadecyltrimethylammonium bromide in water, react for 10 to 15 hours, filter to obtain a precipitate; wash and dry the precipitate, and then calcine under an inert atmosphere to obtain a calcined product; Wherein, the molar ratio of Co salt, Zn salt, 2-methylimidazole and hexadecyltrimethylammonium bromide is (45-55):(140-160):(5-7):(1000-1100); The molar volume ratio of Co salt and water is (9×10 -6 ~1.1×10 -5 )mol:(160~170)mL.
4. The method for preparing the nanozyme according to claim 1, wherein: The precipitate is calcined in an inert atmosphere to obtain a calcined product, specifically comprising: heating the precipitate from room temperature to 700-800° C. at a rate of 5-7° C. / min in the inert atmosphere, calcining for 2-3 hours, and then cooling to room temperature to obtain a calcined product; The inert atmosphere includes at least one of nitrogen, helium, neon and argon.
5. The method for preparing the nanozyme according to claim 1, characterized in that: The calcined product and Ru salt are added to ethylene glycol, heated at 170-180° C. for reaction for 3-5 hours, and filtered to obtain the nanomaterial; Dissolve the nanomaterial and glucose oxidase in water, stir for 2 to 3 hours, and filter to obtain the nanozyme; The mass ratio of the calcined product to the Ru salt is (8-10):(5-6), and the mass volume ratio of the Ru salt to the ethylene glycol is (25-30) mg:(50-55) mL; The mass ratio of the nano material to the glucose oxidase is (2-3):(1-2), and the mass volume ratio of the glucose oxidase to water is (10-20) mg:(60-65) mL.
6. A nanozyme, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 5.
7. Use of the nanozyme as claimed in claim 6 in detecting glucose concentration.
8. A method for detecting glucose concentration, characterized in that: The following steps are involved: Adding the nanozyme and TMB according to claim 6 to the test solution to obtain a mixed solution; Add acetic acid-sodium acetate buffer to the mixed solution, incubate, and measure the absorbance at 652 nm; The glucose concentration was detected by absorbance.
9. The method for detecting glucose concentration according to claim 8, wherein: The volume ratio of the mixed solution to the acetic acid-sodium acetate buffer solution is (3-5):(17-20); The pH value of the acetic acid-sodium acetate buffer is 4.0 to 6.0; The incubation temperature is 20-40° C. and the incubation time is 20-25 min.
10. The method for detecting glucose concentration according to claim 8, wherein: The concentration of the nanozyme in the mixed solution is 0.02-0.1 mg / mL; The concentration of TMB in the mixed solution is 2-10 mM.
Citation Information
Cited By
Method for detecting glucose based on cerium dioxide / gold nanocluster-Prussian blue nanoenzyme cascade catalysis
CN121253739A